Pengaruh Pemberian Berbagai Konsentrasi NAA (Naphthalene Acetic Acid) dan BAP (Benzyl Amino Purine) terhadap Multiplikasi Tunas Tanaman Tebu (Saccharum Officinarum L.) - Isna Lutfiani; Ani Lestari; Nurcahyo Widyodaru; Sri Suhesti (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2022)
Sugarcane (Saccharum officinarum L.) is one of the plantation commodities that have high economic value because it is the main raw material in the manufacture of sugar. Generally, sugarcane propagation was done by vegetative cuttings, but this method has drawbacks. In vitro plant, culture is an alternative technique for producing quality sugarcane seed, a high number of seeds with shoot multiplication. This research aims to review the influence of concentration NAA and BAP on shoot multiplication of sugarcane (Saccharum officinarum L.). The study was conducted in the Laboratory of Superior Farm Seed Management Unit, Indonesian Agency for Agricultural Research and Development from June until August 2021. Explant material used was young rolled leaves collected from AMS variety sugarcane. The experiment was arranged in Factorial Completely Randomized Design (RAL), with 12 treatments, and five replication. Explants were cultured during 8 weeks in MS media with concentration NAA ( 0 ppm, 0.5 ppm, and 1 ppm), and BAP (0 ppm, 1 ppm, and 2 ppm, 3 ppm). The parameters measured were the date of shoot initiation, number of shoots, length of shoot, number of leaves, date of root initiation, number of the root, length of root, and color of the shoot. The data were analyzed using ANOVA at the confidence level of 95%. The results showed that interaction between NAA and BAP in promoting Saccharum officinarum L. Micro cutting growth was observed. The combination between NAA of 0 ppm and BAP of 2 ppm was found to be the best in date of shoot initiation, number of shoots, and number of the leaf. The combination between NAA 1 ppm and BAP 0 ppm was recommended to promote the root number and length of the root.